OP70 Wealth differences in age-trajectories of body size: findings from the english longitudinal study of ageing. (2nd September 2017) - Lassale, C; Steptoe, A; Zaninotto, P
Abstract : Background: While the obesity epidemic has devastating health consequences at all ages, underweight is also associated with an increased mortality risk. Lower socioeconomic status is associated with higher obesity rates and greater weight gain, but evidence from prospective studies in older adults is scarce. Our aim was to describe age-trajectories of body mass index (BMI) and waist circumference (WC) in a population-based study of older adults in England and to assess the association with wealth. Methods: Data come from a nationally representative sample of 3259 men and 3966 women aged 52y and over from the English Longitudinal Study of Ageing (ELSA) who had a measurement of BMI and WC on three occasions (2004–2005; 2008–2009; 2012–2013). We used latent growth curve modelling to estimate baseline status (intercept) and rate of change (linear slope) interpreted as the change per year. Intercept and slope were regressed on wealth tertile, and covariates (age, ethnicity, marital status, physical inactivity, smoking status and limiting long-standing illness). Gender- and age-specific (<70, ≥70 y) models were fitted. Results: In the <70 y group, a man aged 60y in the richest wealth tertile had a baseline BMI of 27.7kg/m 2 and WC of 100.5 cm and a woman a BMI of 26.9kg/m 2 and WC of 88.2 cm. BMI increased by 0.04 kg/m 2 every year in men and 0.05kg/m 2 in women; and WC increased by 0.15 cm/year in men and 0.21 cm/year in women. Being in the poorest wealth group was associated with highest baseline BMI (28.7kg/m 2 for men and 29.4kg/m 2 for women) and WC (103.1 cm in men and 93.6 cm in women). However, there was no difference in the rate of change between those in the richest and poorest wealth tertiles. In the ≥70 y group, for a man aged 77y in the richest tertile, the baseline BMI was 26.7kg/m 2 and WC 100.0 cm and for a woman it was 26.3kg/m 2 and 88.7 cm. The rate of change was non-significant for both anthropometrics markers. An individual of the same age in the poorest tertile had higher baseline BMI and WC (man: 27.5kg/m 2 and 102.1 cm; woman: 28.1kg/m 2 and 92.1 cm). Conclusion: In this population-based study, BMI and WC increased significantly over time in both men and women until the age of 70, thereafter it remained stable. Less wealth was strongly associated with a higher BMI and WC at any given age, however the rates of change were similar, indicating that the socioeconomic gap associated with excess adiposity did not close with ageing.